An Investigation of the Influencing Success Factors among Indian Managers within the Malaysian Insurance Industry - Thangaras, Selvamalar (2006)
In today’s world insurance is necessary for protection against financial risks that may arise at any point of time in life. Many types of insurance have been developed to cover the unexpected. For instance life insurance covers poor health, disablement and death whereas general insurance covers damages caused to motor vehicles and properties by accident, fire or natural disasters. With the increasing demand insurance now provides more than just protection as it may include savings or investment programme. In Malaysia, the rapid development of the product is highly contributed by the continuous growth of the insurance industry. Increasing numbers of migrants from India who have come to Malaysia during the British establishment are moving into this industry to establish their careers. With the development of the insurance industry most of them have also managed to secure top positions within the industry and thereafter became highly successful. Their fast progress within the industry was also found to be an interesting fact but however, there were no previous research carried out to address this issue. As such, with much research and in-depth study the query is brought about in three separate aspects i.e. to identify the factors that contributed towards the success of these Indian managers, to analyze their future and potentials in this industry, and to identify the benefits of their progress to Malaysia as well as the measurers that Malaysia can take in support of this in the next 5 years. Hence, this research will answer these questions in detail so as to provide a valuable source of information to those within the insurance industry and also as a source reference for future researches.